The Relationship Between Social Media Digitalization and Coronavirus Disease 2019 Fear Among Service Sector Employees - Wang, Kai; Lin, Kejun; Yang, Shixin; Na, Sang-Gyun (Frontiers in Psychology, 2021)
In the age of digitalization, social media has played a significant role in quickly spreading the news about current affairs. From December 2019 to now, COVID-19, with its several mutated shapes, has more transmissible potential catastrophe and has become a severe phenomenon issue worldwide. The international spread of the epidemic has created fear among people, especially employees working physically in different organizations. The present research aimed to measure the impact of social media on its users in the People's Republic of China. The social media users more often got influenced by shocking news instructively and destructively. The research analysis was based on service sector employees and data collected from 630 respondents via a structured questionnaire. This research confirmed the negative impact of fear on social media on employee’s performance. This research also confirmed the moderation impact of the COVID-19 vaccine on the relationship between social media fear and employee performance. This research recommends that the China censor board check the news and its validity to reduce the fear of COVID-19 among employees. This research will become a roadmap for organizations and media controllers to understand the impact of social media during an intense situation. The telecommunication sector will reduce psychological disease and enhance the work capability of employees by controlling unnecessary and unapproved material about sensitive issues.